The influence of the geomorphological factors on the relief modelling within Eselnita hydrographic basin (Danube catchment/Romania) - DANIELA VLAD; RALUCA-GEORGIANA ALEXANDRU (Cinq Continents, 2012)
Developed on the south-eastern side of Almãjului Mountains, Eşelniţa drainage basin neighbours upon the following basins: upon S – SV with Mala, upon SV - V with Mraconia, upon V – NV with Berzasca, upon NV - NNE with Nera and on the NNE – SE direction with Cerna. The basin has a surface of 77 km2 and present a 5th degree hydrographic network according to Horton-Strahler ranking system, tributary to Danube by means of Eşelniţa main collector. Developed in a mountain landscape, the basin presents different levels held between minimum altitude of 64 m at the confluence with the Danube and maximum altitude of 1107 m, thus presenting a difference of 1043 m. Geological formations within the basin belong predominant to the Danubian Domain, so in central and upper courses, these are represented by a crystalline foundation and by magmatic rocks of intrusive nature covered by very small areas of sediment located in the northwest (belong to the Lower Jurassic) and in the south-eastern (belongs to the Upper Cretaceous) of the basin. But in the lower course, there are both crystalline and the sedimentary formations, last being integrated to Orşova depression and whose presence is related to the evolution of the Danube. Morphometric indices of Eşelniţa basin allows the distinction of a higher sector, mountainous terrain with high energy under a relatively increased fragmentation and depression sector with low relief energy and also with an intense fragmentation of the existing sedimentary rocks wich favors erosion manifestation in the context of deforestation action.